Paraquat poisoning: Experience of an Internal Medicine department - Branco, Vítor (2001)
Aims: To study the presentation, treatment andevolution of Paraquat poisoning, looking forprognostic indicators.Material and Methods: A retrospective analysis ofParaquat poisoning cases admitted to an InternalMedicine department between January 1987 andJanuary 2000, using a data collection protocol, wasmade. The following parameters were assessed:demographic; quantity ingested and time fromingestion to hospital arrival; evolution and mortality;clinical manifestations and results of laboratorial testson and during admission; treatments instituted.Results: 37 cases were documented: 19 died(51.4%) after a mean time of 7 days, 18 survived(48,6%) after a mean follow up of 7.5 months. Theappearance of jaundice, leucocytosis, renal failureand hypoxaemia was significantly more frequent inthe patients who died. High values of lacticdehydrogenase and low values of carbon dioxideon admission were associated with worse prognosis.Among the various treatment modalities used,sodium sulphate, either isolated or associated withgastric lavage and activated charcoal, had astatistically significant favourable effect on survival(used in 31% of the deceased and 55% of survivors).Haemocarboperfusion was used more frequently inthe group of deceased patients (58% against 33%).Other dialysis techniques were used infrequently.Conclusions: The best prognostic indicator(paraquatemia) was not available in our series.Mortality correlates with the quantity of poisoningested, resulting acutely from multi-organ failure,or from late respiratory failure. Adsorbents andcathartics are still the only confirmed prognosticmodifiers. Advantages of other therapeutic modalities, such as dialytic techniques, were notfound in this study.